Zirconium-based metal organic framework material molding material, its manufacturing method and its application method
By combining the zirconium-based metal organic framework material with organic binder and preparing molded materials by flash freezing and vacuum drying processes, the problem of unstable metal organic framework material in the prior art is solved, and efficient adsorption and stable water treatment effects are achieved.
Patent Information
- Application Number
- CN202010935419.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-09-08
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2040-09-08
AI Technical Summary
The existing metal organic framework materials have problems such as swelling and dispersion in water treatment, which leads to instability in water, and the powdered materials are difficult to separate after adsorbing pollutants, which may cause secondary pollution.
The zirconium-based metal organic framework material is combined with organic binder, and the molded materials are prepared by flash freezing and vacuum drying processes to form a porous structure to improve adsorption rate and stability in water.
It realizes efficient adsorption of highly toxic anionic pollutants in water, improves the adsorption rate, and ensures stability in water, so that the material is easily separated and regenerated after adsorption.
Abstract
Description
Technical Field
[0001] The invention relates to a zirconium-based metal organic framework material molding material, a manufacturing method and an application method thereof. Background Art
[0002] Metal organic framework materials (hereinafter, sometimes also referred to as MOFs) are porous materials with a three-dimensional network structure formed by metal ions and organic ligands. Such metal organic framework materials have the characteristics of large surface area, low density, and high structural adjustability. Therefore, MOFs are used in many scientific and technological fields, such as gas adsorption and separation, gas storage, catalysis, drug release, electromagnetic induction, electronics, etc., especially in catalysis, gas adsorption and separation, gas storage, etc.
[0003] For example, in Finsy V, ma L, Alaerts L et al., Separation of CO2 / CH4 mixtures withthem IL-53(Al) metal–organic framework, Microporous and mesoporous materials, 2009, Vol. 120(3): 221-227, particulate MIL-53(Al) was made into small particles using a 15% by weight aqueous solution of PVA (polyvinyl alcohol) as a binder, and the obtained small particles were pressed into a column, and a mixed gas of carbon dioxide and methane was passed through the column, thereby utilizing the screening effect of MOFs to separate carbon dioxide and methane.
[0004] In Zheng J, Cui X, Yang Q et al., Shaping of ultrahigh-loading MOF pellet with a strongly anti-tearing binder for gas separation and storage, Chemical Engineering Journal, 2018, Vol. 354: 1075-1082, PVB (polyvinyl butyral) was used as a strong tear-resistant and highly viscous binder to shape four anionic columnar ultramicroporous materials (SIFSIX-3-Ni, SIFSIX-2-Cu-i, geFSIX-2-Cu-i (ZU-32), TIFSIX-2-Cu-i) into small particles and used for gas separation and storage.
[0005] In Zhuh, Yang X, Cranston ED, et al., Flexible and Porous nanocellulose Aerogel with high Loadings of metal–Organic-Framework Particles for Separations Applications. Advanced materials, 2016, Vol. 28(35): 7652-7657, the granulation of several typical metal organic framework materials including UiO-66 was studied.
[0006] In the past, MOFs materials were mostly used for gas separation, absorption and storage, drug release and catalysis. However, in recent years, based on their function as porous structures, the demand for applying MOFs materials to water treatment has gradually increased. It is expected that anionic pollutants such as heavy metal oxyacids in water can be removed through the adsorption effect of MOFs.
[0007] However, previous MOFs materials sometimes swell and disperse when used in water treatment, resulting in increased turbidity in the water, making it difficult to meet the stability requirements for water treatment.
[0008] Moreover, in the past applications of MOFs materials, in many cases, MOFs materials were used in the form of powders, and the particle size of these MOFs material powders ranged from tens of nanometers to several micrometers, and the largest particle size was only micrometers. Such powdered materials are usually dense, and after adsorbing pollutants, the required pressure for separation and regeneration is relatively high. Moreover, since powdered MOFs materials are difficult to separate from water after adsorbing pollutants, they may also cause secondary pollution.
[0009] In addition, in the past, the molding process of metal organic framework materials usually adopts ordinary drying at 100-500℃. However, the metal organic framework molding materials that have been dried by ordinary drying will shrink during drying, often becoming harder and denser, and the specific surface area will decrease, thus affecting the adsorption rate of pollutants. In addition, when freeze drying at about -50℃ is used to manufacture metal organic framework molding materials, there are also problems such as poor molding effect and inability to form regular particles. Summary of the invention
[0010] Technical Problems to be Solved by the Invention
[0011] The present invention is completed in view of the above situation, and its purpose is to provide a zirconium-based metal organic framework material molding material with excellent stability in water and capable of increasing the adsorption rate when adsorbing highly toxic anionic pollutants in water, as well as a manufacturing method and application method of the molding material.
[0012] In order to achieve the above object, the present invention provides the following solutions.
[0013] [1] A zirconium-based metal organic framework material molding material, comprising a zirconium-based metal organic framework material and an organic binder.
[0014] [2] The zirconium-based metal organic framework molding material according to claim [1], wherein the zirconium-based metal organic framework material contains zirconium ions and organic ligands.
[0015] [3] According to the zirconium-based metal organic framework molding material according to claim [2], the organic ligand is selected from one or more of 1,3,5-benzenetricarboxylic acid, 1,4-phthalic acid and fumaric acid.
[0016] [4] The zirconium-based metal organic framework molding material according to any one of claims [1] to [3], wherein the mass of the zirconium-based metal organic framework material accounts for 20 to 80% of the total mass of the zirconium-based metal organic framework molding material;
[0017] The zirconium-based metal organic framework material molding material is a porous structure with a specific surface area of 326 to 628 m 2 / g, and the average pore size is 1.9~2.8nm.
[0018] [5] According to any one of claims [1] to [4], the zirconium-based metal organic framework molding material, the organic binder contains one or more selected from carboxymethyl cellulose, sodium alginate, and polyvinyl alcohol.
[0019] [6] A method for manufacturing a zirconium-based metal organic framework molding material, comprising the following steps:
[0020] (a) preparing metal organic framework powder materials,
[0021] (b) after preparing an organic binder solution, adding the metal organic framework powder material obtained in step (a) to the organic binder solution and uniformly dispersing the powder material to obtain a suspension containing particles as a precursor of a MOFs molding material,
[0022] (c) separating the particles from the suspension and drying them to obtain a zirconium-based metal organic framework molding material.
[0023] [7] According to the method for manufacturing a zirconium-based metal organic framework molding material described in [6], the solution of the organic binder used in step (b) is a solution containing one or more organic binders selected from carboxymethyl cellulose, alginic acid, and polyvinyl alcohol.
[0024] [8] According to the method for manufacturing zirconium-based metal organic framework molding materials described in [6] or [7], in step (c), the drying is performed by freezing by flash freezing and then vacuum drying, and the flash freezing method is to immediately place the particles separated from the suspension at a temperature below -180°C and maintain it.
[0025] [9] According to the method for manufacturing a zirconium-based metal organic framework molding material described in [8], the flash freezing method is to directly place the particles into liquid nitrogen and keep them for more than 0.5 hours.
[0026]
[10] A method for applying a zirconium-based metal organic framework material molding material, wherein the metal framework material molding material described in [1] to [5] is directly brought into contact with contaminated water to adsorb highly toxic anionic pollutants contained in the water.
[0027]
[11] According to the application method of the zirconium-based metal organic framework molding material described in
[10] , the highly toxic anionic pollutants are heavy metals, heavy metal oxygenates, hydrochlorides, phosphates, and fluoride ions.
[0028] Effects of the Invention
[0029] Compared with the previous zirconium-based MOFs molding material manufacturing method, the manufacturing method of the zirconium-based metal organic framework material of the present invention can prevent the zirconium-based MOFs molding material from becoming dense during the molding process, thereby preventing the specific surface area of the zirconium-based MOFs molding material from being reduced, and preventing the zirconium-based MOFs molding material from becoming unstable in water. In other words, the zirconium-based MOFs molding material manufactured by the manufacturing method of the zirconium-based MOFs molding material of the present invention can make full use of the internal structure of the obtained molding material, can increase the adsorption rate of pollutants, and can ensure stability in water. DETAILED DESCRIPTION
[0030] Specific embodiments of the present invention will be described below, but the present invention is not limited to these specific embodiments.
[0031] An embodiment of the present invention relates to a zirconium-based metal organic framework material molding material, which includes a zirconium-based metal organic framework material and an organic binder.
[0032] [Zirconium-based metal-organic framework materials]
[0033] The zirconium-based metal organic framework material of the present invention contains zirconium ions and organic ligands. The zirconium ions and the organic ligands are combined through coordination bonds to form the zirconium-based metal organic framework material with a porous structure.
[0034] The organic ligand used in the present invention may be a substituted or unsubstituted mono- or poly-carboxylic acid compound, for example, various compounds such as formic acid, acetic acid, propionic acid, oxalic acid, malonic acid, fumaric acid, 1,3-phthalic acid, 1,4-phthalic acid, 1,3,5-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4,5-benzenetetracarboxylic acid, 2,6-naphthalene dicarboxylic acid, 9,10-anthracene dicarboxylic acid, trans,trans-muconic acid, cis,cis-muconic acid, 2-amino-1,4-phthalic acid, 4,4'-ethynylene dibenzoic acid, 2,2'-diamino-4,4'-stilbene dicarboxylic acid, 2,2'-dinitro-4,4'-stilbene dicarboxylic acid, 2,3-pyrazine dicarboxylic acid, etc. may be used alone or in combination of multiple compounds.
[0035] Among them, from the viewpoint of improving the stability in water and the anionic pollutant adsorption effect, one or more selected from 1,3,5-benzenetricarboxylic acid, 1,4-phthalic acid and fumaric acid are preferred.
[0036] [Organic binder]
[0037] The organic binder used in the present invention is not particularly limited as long as it is an organic binder compound that can shape the material to be formed into a desired shape. For example, alkoxysilanes such as tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetrabutoxysilane, trimethoxysilane, triethoxysilane, tripropoxysilane, and tributoxysilane can be used; alkoxy titanates such as tetramethoxy titanate, tetraethoxy titanate, tetrapropoxy titanate, tetrabutoxy titanate, trimethoxy titanate, triethoxy titanate, tripropoxy titanate, and tributoxy titanate can be used; cellulose derivatives such as sodium methyl cellulose, sodium carboxymethyl cellulose, and sodium hydroxypropyl methyl cellulose; sodium alginate; gelatin; polyvinyl alcohol, etc. These organic binders can be used alone or in combination.
[0038] Zirconium-based MOFs molding materials using organic binders have better stability in water compared to those using inorganic binders such as diatomaceous earth and kaolin. When placed in water to adsorb pollutants, they are not easily released and enter the water, thus avoiding the increase of turbidity in the water.
[0039] In view of availability, cost, etc., the above-mentioned organic binders are further preferably selected from one or more of sodium carboxymethyl cellulose, sodium alginate, and polyvinyl alcohol.
[0040] [Forming materials for zirconium-based metal-organic framework materials]
[0041] The zirconium-based MOFs molding material of the present invention is obtained by bonding the zirconium-based metal organic framework material with the above-mentioned binder, and its shape is not particularly limited as long as it can be used to adsorb pollutants after molding. For example, it can be various three-dimensional shapes such as particles and films.
[0042] The specific surface area of the zirconium-based MOFs molding material of the present invention is 326 to 628 m 2 / g, the average pore size is 1.9-2.8nm. If the specific surface area is less than 326m 2 / g, it will affect the adsorption efficiency of pollutants in water and cause the adsorption rate to decrease.
[0043] When the zirconium-based MOFs molding material of the present invention is in the form of particles, the particle size thereof is greater than 1 mm, preferably 1 mm to 10 mm.
[0044] It should be noted that the particle size of the zirconium-based MOFs molding material of the present invention is obtained by observing the particles of the zirconium-based metal organic framework molding material using a scanning electron microscope (SEM).
[0045] Since the zirconium-based MOFs molding material of the present invention has large particles and a relatively loose internal structure, it can fully utilize the internal microporous structure and improve the ability to adsorb pollutants. In addition, after adsorbing pollutants in water, it is easy to separate them from the water, and further, the separation and regeneration treatment after adsorbing pollutants is also very easy.
[0046] [Measurement method of specific surface area]
[0047] The specific surface area of the zirconium-based MOFs molding material of the present invention can be calculated by a nitrogen adsorption method, specifically: a sample of the zirconium-based MOFs molding material is prepared by the following method for manufacturing the zirconium-based MOFs molding material, the sample is degassed at 150°C for 12 hours, the nitrogen adsorption and desorption performance is tested at liquid nitrogen temperature, and the specific surface area of the sample is calculated by the BET method.
[0048] [Method for measuring average pore diameter]
[0049] The average pore size of the zirconium-based MOFs molding material of the present invention can be calculated using the above-mentioned nitrogen adsorption method, specifically: preparing a sample by the same method as above, and testing the nitrogen adsorption and desorption performance, calculating the pore size distribution using the BET (4V / A) method, and calculating the average pore size based on the pore size distribution.
[0050] [Method for producing zirconium-based metal organic framework molding material]
[0051] Another embodiment of the present invention relates to a method for preparing a zirconium-based metal organic framework material. The method for preparing a zirconium-based metal organic framework material comprises the following steps:
[0052] (a) Preparation of zirconium-based metal-organic framework powder materials
[0053] The source material of zirconium ions and the source material of organic ligands are dissolved in the solvent in sequence, and then acetic acid and deionized water are added respectively, and mixed and stirred for 10 to 30 minutes, and then sealed and microwave heated to 120 to 150°C for 15 to 60 minutes. After the reaction is completed, the solid is centrifuged and washed three times with DMF and ethanol respectively, and vacuum dried at 60°C for 12 to 24 hours to obtain a powdered metal organic framework powder material.
[0054] The compound serving as a source material of zirconium ions may be a zirconium halide, for example, zirconium chloride may be used.
[0055] As the source material of the organic ligand, various substituted or unsubstituted mono- or polycarboxylic acid compounds as mentioned above can be used.
[0056] The solvent used is not limited, and common solvents such as N,N-dimethylformamide (DMF) and N,N-dimethylacetamide (DEF) can be used.
[0057] It should be noted that the method for obtaining metal organic framework powder material is not limited to the above-mentioned method using microwave synthesis, and various methods such as commonly used organic solvent volatilization method, high temperature solid phase method, hydrothermal method, diffusion method, etc. can also be used to prepare metal organic framework powder material.
[0058] (b) Preparing a binder solution and a suspension of a zirconium-based metal-organic framework material
[0059] Prepare an aqueous solution of the above binder with a concentration of 0.5-1.5wt%. Then, add the zirconium-based metal organic framework powder material obtained in step (a) to the binder solution in a certain proportion and disperse it as evenly as possible, let it stand for 5-30 minutes, extrude it into a molding solution for molding, and mold it for 10-30 minutes, thereby obtaining a suspension containing particles as a precursor of the zirconium-based MOFs molding material.
[0060] Among them, when the zirconium-based metal-organic framework powder material is dispersed uniformly, various equipment such as a homogenizer, a disperser, and a mixer can be used.
[0061] There are no particular restrictions on the above-mentioned molding solution. For example, solutions of calcium salts, magnesium salts, and aluminum salts can be used. Considering the solubility, solutions of calcium chloride, magnesium chloride, aluminum chloride, aluminum sulfate, calcium nitrate, magnesium nitrate, and aluminum nitrate are preferably used. Considering the safety aspect, solutions of calcium chloride, magnesium chloride, aluminum chloride, and aluminum sulfate are more preferably used.
[0062] (c) Obtaining a Zirconium-based Metal-Organic Framework Molding Material
[0063] The formed particles are separated from the above suspension and dried to obtain a zirconium-based MOFs molding material. Among them, the drying method adopts flash freezing and vacuum drying. Flash freezing is a method of freezing at a faster speed and lower temperature compared to the previous freeze drying. Specifically, the particles separated from the calcium chloride solution (i.e., the zirconium-based MOFs molding material precursor) can be immediately placed in an environment below -180°C and maintained. The specific conditions such as the means of achieving flash freezing, the time of flash freezing, the temperature and time of vacuum drying can be specifically determined according to the characteristics of the desired product.
[0064] For example, the zirconium-based MOFs molding material precursor can be placed in liquid nitrogen and frozen for more than 0.5 hours, and then vacuum dried for 12 to 48 hours. Preferably, liquid nitrogen is used for flash freezing for more than 1 hour, and vacuum dried for 24 to 48 hours.
[0065] After the above drying, the desired zirconium-based MOFs molding material can be obtained.
[0066] As a method for separating the formed particulate matter from the above-mentioned suspension, a common method such as filtration can be used.
[0067] In the obtained zirconium-based MOFs molding material, the mass ratio of the metal organic framework material to the total molding material will be different depending on the molding material used.
[0068] For example, the mass of the zirconium-based metal organic framework material accounts for about 20% to 80% of the total mass of the zirconium-based metal organic framework material molding material, preferably 30% to 70%, and more preferably 33% to 67%.
[0069] [Application method of zirconium-based metal organic framework molding materials]
[0070] Another embodiment of the present invention relates to an application method of a zirconium-based metal organic framework material. The zirconium-based metal organic framework material can be used to adsorb pollutants present in water, and the pollutants are not particularly limited, for example, they can be highly toxic anionic pollutants such as heavy metals, heavy metal oxyacid salts, hydrochlorides, phosphates, and fluoride ions.
[0071] In addition, the application method of the zirconium-based metal organic framework material molding material of the present invention is not particularly limited. It can be directly contacted with polluted water. For example, it can be directly placed in industrial sewage or domestic sewage in the form of particles for use. The zirconium-based metal organic framework material molding material of the present invention can also be made into a column and used in the form of an adsorption column.
[0072] Example
[0073] Example 1
[0074] 291 mg of zirconium chloride and 208 mg of 1,4-benzenedicarboxylic acid were dissolved in 10 mL of n,N-dimethylformamide (DMF) in sequence, and then 2.1 mL of acetic acid and 0.135 mL of deionized water were added respectively. After mixing and stirring for 15 minutes, the mixture was sealed and microwaved to 120°C for 15 minutes. The microwave power at this time was 350 W. After the reaction was completed, the solid was separated by centrifugation, washed three times with DMF and ethanol respectively, and dried in vacuum at 60°C for 12 hours to obtain a powdered zirconium-based metal organic framework powder material (UiO-66(Zr)).
[0075] Prepare a sodium alginate solution with a concentration of 0.5wt% and a calcium chloride solution with a concentration of 2.5wt%. Add the obtained zirconium-based metal organic framework powder material (UiO-66 (Zr)) to the sodium alginate solution at a mass ratio of 50% (the ratio of UiO-66 (Zr) powder material to the total mass of sodium alginate and UiO-66 (Zr) powder material), use a homogenizer to disperse it as evenly as possible, let it stand for 5 minutes, extrude it into the calcium chloride solution for molding, and mold it for 10 minutes. Separate the formed particles from the calcium chloride solution, immediately put it into liquid nitrogen, freeze it for 1 hour, and then vacuum dry it for 24 hours to obtain the MOFs molding material of Example 1. The particle size of the obtained zirconium-based MOFs molding material is 1.5mm, and the specific surface area is 570m 2 / g, and the average pore size is 2.30nm.
[0076] [Pollution adsorption rate]
[0077] Arsenate was used as a highly toxic anionic pollutant to confirm the pollutant adsorption effect of the MOFs molding material obtained in Example 1.
[0078] Prepare 100 mL of a solution containing an initial arsenate concentration of 20.0 mg / L in a conical flask, and adjust the initial pH of the solution to 7.0. Add 100 mg of the zirconium-based MOFs molding material obtained in Example 1, place the conical flask in a full-temperature oscillating incubator (HZQ-F160), maintain the temperature in the incubator at 25°C, react at an oscillation rate of 200 rpm, take 5 mL of samples at 1, 3, 6, 12, and 24 hours, filter through a 0.22 μm filter membrane, and use inductively coupled plasma emission spectrometry to determine the concentration of residual arsenate in the filtrate and calculate the adsorption amount of the adsorbent, which is fitted by a pseudo-second-order kinetic equation. As a result, the arsenate adsorption rate of the zirconium-based MOFs molding material in Example 1 is 0.033 g / h·mg.
[0079] [Stability in water]
[0080] The zirconium-based MOFs molding material of Example 1 was placed in pure water at 25°C and 200 rpm shaking conditions, and visually observed at various time periods whether the zirconium-based MOFs molding material began to swell and disperse in the water, and whether cracks appeared in the zirconium-based MOFs molding material.
[0081] As a result, the zirconium-based MOFs molded material of Example 1 was not observed to swell and disperse even after one day in water, and no cracks were observed.
[0082] Example 2
[0083] The organic ligand was changed to 1,3,5-benzenetricarboxylic acid, that is, 70 mg of zirconium chloride and 233 mg of 1,3,5-benzenetricarboxylic acid were dissolved in 15 mL of n,N-dimethylformamide (DMF) DMF solvent, and 15 mL of formic acid was added respectively. After mixing and stirring for 15 minutes, the mixture was sealed and microwaved to 120°C for 15 minutes. The microwave power at this time was 350 W. After the reaction was completed, the solid was separated by centrifugation, washed three times with DMF and ethanol respectively, and dried in vacuum at 60°C for 12 hours to obtain a powdered zirconium-based metal organic framework powder material.
[0084] Then, prepare a sodium alginate solution with a concentration of 0.5wt% and a calcium chloride solution with a concentration of 2.5wt%. Add the powdered zirconium-based metal organic framework material to the sodium alginate solution at a ratio of 50% of the total mass of the sodium alginate and the zirconium-based metal organic framework material, use a homogenizer to disperse it as evenly as possible, let it stand for 5 minutes, extrude it into the calcium chloride solution for molding, and mold it for 10 minutes. Separate the formed granules from the calcium chloride solution, put it into liquid nitrogen, cool it for 2 hours, and vacuum dry it for 24 hours to obtain the zirconium-based MOFs molding material of Example 2. The obtained MOFs molding material has a particle size of 1.5mm and a specific surface area of 628m 2 / g, and the average pore size is 2.8nm.
[0085] The pollutant adsorption rate and stability in water of the zirconium-based MOFs molding material of Example 2 were confirmed by the same test method as Example 1. As a result, the arsenate adsorption rate of the zirconium-based MOFs molding material of Example 2 was 0.045 g / h·mg. No swelling or dispersion was observed in the zirconium-based MOFs molding material of Example 2 after one day in water, and no cracks were observed.
[0086] Example 3
[0087] The zirconium-based metal organic framework powder material was prepared by the same method as in Example 1. Then, 1wt% sodium carboxymethyl cellulose was used as an organic binder and 4wt% polyvinyl alcohol was used as a cross-linking agent. The powdered zirconium-based metal organic framework material was added to the sodium carboxymethyl cellulose and polyvinyl alcohol solution at a ratio of 50%, and was dispersed as evenly as possible using a homogenizer. After standing for 5 minutes, it was extruded into an aluminum sulfate solution for molding. The molding lasted for 10 minutes. The formed granules were separated from the aluminum sulfate solution, placed in liquid nitrogen, cooled for 2 hours, and vacuum dried for 24 hours to obtain the zirconium-based MOFs molding material of Example 3. The particle size of the obtained zirconium-based MOFs molding material was 1.3 mm, and the specific surface area was 501 m 2 / g, and the average pore diameter is 1.9nm.
[0088] The pollutant adsorption rate and stability in water of the zirconium-based MOFs molded material of Example 3 were confirmed by the same test method as Example 1. As a result, the arsenate adsorption rate of the MOFs molded material of Example 3 was 0.022 g / h·mg. No swelling or dispersion was observed in the zirconium-based MOFs molded material of Example 3 after one day in water, and no cracks were observed.
[0089] Comparative Example 1
[0090] The zirconium-based metal organic framework material powder material was prepared by the same method as in Example 1, and the sodium alginate solution and the calcium chloride solution were prepared with the same concentrations as in Example 1. In addition, the particles suspended in the calcium chloride solution were prepared by the same operation as in Example 1. Then, the particles separated from the suspension were frozen in the freezing chamber (-50°C) of the freeze dryer for 12 hours, and then vacuum dried at room temperature for 24 hours, thereby preparing a freeze-dried zirconium-based metal organic framework material molding material.
[0091] The zirconium-based MOFs molding material obtained in Comparative Example 1 has a poor molding effect, and basically forms a dense sheet but cannot form a regular particle. Its specific surface area is 297m 2 / g, and the average pore diameter is 2.3nm.
[0092] The pollutant adsorption rate and stability in water of the zirconium-based MOFs molding material of Comparative Example 1 were confirmed by the same test method as Example 1. As a result, the arsenate adsorption rate of the zirconium-based MOFs molding material of Comparative Example 1 was 0.009 g / h·mg. In addition, the zirconium-based MOFs molding material of Comparative Example 1 began to swell and disperse in water after 3 hours, and the degree of cracking of the material was very large, and it was unstable in water.
[0093] Comparative Example 2
[0094] Using 33wt% diatomaceous earth or kaolin as an inorganic binder, the UiO-66 (Zr) obtained in Example 1 and the inorganic additive were first thoroughly mixed in a mortar and then granulated. After completion, the mixture was dried by flash freezing to obtain a zirconium-based MOFs molding material. The obtained zirconium-based MOFs molding material had a particle size of 2.0 mm and a specific surface area of 436 m 2 / g, and the average pore diameter is 3.3nm.
[0095] The pollutant adsorption rate and stability in water of the zirconium-based MOFs molded material of Comparative Example 2 were confirmed by the same test method as Example 1. As a result, the arsenate adsorption rate of the zirconium-based MOFs molded material of Comparative Example 2 was 0.021 g / h·mg.
[0096] It should be noted that although the zirconium-based MOFs molding material of Comparative Example 2 has a relatively good adsorption rate, the binder is released and enters the water after being placed in water for 6 hours, resulting in increased turbidity in the water. This is because the zirconium-based MOFs molding material of Comparative Example 2 using an inorganic binder can be formed into particles, but its structure is easily destroyed and is unstable in water, so it is not practical.
[0097] Comparative Example 3
[0098] The zirconium-based metal organic framework powder material was prepared by the same method as in Example 1, and the sodium alginate solution and the calcium chloride solution were prepared with the same concentrations as in Example 1. In addition, the particles suspended in the calcium chloride solution were prepared by the same operation as in Example 1. Then, the obtained particles were dried at 105°C for 24 hours using a conventional heating drying method, i.e., an electric heating blast drying oven device, to prepare a conventionally dried MOFs molding material.
[0099] The particle size of the obtained MOFs molding material is 1.0 mm and the specific surface area is 40 m 2 / g, the average pore size is 2.9nm, and the arsenate adsorption rate is 0.006g / h·mg.
[0100] It can be seen that the zirconium-based metal organic framework molding material of the present invention adopts flash freezing in its manufacturing process. Therefore, compared with the MOFs molding materials prepared by conventional drying and freeze drying, the adsorption rate of anionic pollutants is improved and it shows excellent stability in water.
[0101] In addition, the zirconium-based metal organic framework material molding material of the present invention has excellent stability in water compared with the MOFs molding material prepared by using an inorganic binder because the organic binder is used.
Claims
1. A method for manufacturing a zirconium-based metal organic framework material molding material, comprising the following steps: (a) preparing metal organic framework powder materials; (b) after preparing a solution of an organic binder, adding the metal organic framework powder material obtained in step (a) into the solution of the organic binder and uniformly dispersing the powder material to obtain a suspension containing particles serving as a precursor of a metal organic framework material forming material; (c) separating the particles from the suspension and drying them to obtain a zirconium-based metal organic framework molding material, In step (c), the drying is performed by freezing by flash freezing and then vacuum drying, wherein the flash freezing method is to immediately place the particles separated from the suspension at a temperature below -180°C and maintain the temperature.
2. According to the method for manufacturing a zirconium-based metal-organic framework molding material according to claim 1, the solution of the organic binder used in step (b) is a solution containing one or more organic binders selected from sodium carboxymethyl cellulose, sodium alginate, and polyvinyl alcohol.
3. The method for manufacturing a zirconium-based metal organic framework molding material according to claim 1 or 2, wherein the flash freezing method is to directly place the particles into liquid nitrogen and keep them for more than 0.5 hours.
4. A zirconium-based metal organic framework material molding material manufactured by the manufacturing method of a zirconium-based metal organic framework material molding material according to any one of claims 1 to 3, comprising a zirconium-based metal organic framework material and an organic binder, wherein the zirconium-based metal organic framework material molding material is a porous structure with a specific surface area of 326 to 628 m 2 / g, an average pore size of 1.9-2.8nm, and the zirconium-based metal organic framework material molding material is granular, and its particle size is greater than 1mm. 5 . The zirconium-based metal organic framework molding material according to claim 4 , wherein the zirconium-based metal organic framework material contains zirconium ions and organic ligands. 6 . The zirconium-based metal organic framework molding material according to claim 5 , wherein the organic ligand is selected from one or more of 1,3,5-benzenetricarboxylic acid, 1,4-phthalic acid and fumaric acid.
7. The zirconium-based metal organic framework molding material according to any one of claims 4 to 6, wherein the mass of the zirconium-based metal organic framework material accounts for 20 to 80% of the total mass of the zirconium-based metal organic framework molding material.
8. The zirconium-based metal organic framework molding material according to any one of claims 4 to 6, wherein the organic binder comprises one or more selected from sodium carboxymethyl cellulose, sodium alginate, and polyvinyl alcohol.
9. A method for applying a zirconium-based metal organic framework molding material, wherein: The metal skeleton material molding material according to any one of claims 4 to 8 is directly brought into contact with polluted water to adsorb highly toxic anionic pollutants. 10 . The application method of the zirconium-based metal organic framework molding material according to claim 9 , wherein the highly toxic anionic pollutants are heavy metal oxygenates, hydrochlorides, phosphates, and fluoride ions.
Citation Information
Patent Citations
Molded metal-organic framework material and molding method thereof
CN107029670A